ANMCO POSITION PAPER: cardio-oncology in the COVID era (CO and CO). (26th August 2021) - Bisceglia, Irma; Gabrielli, Domenico; Canale, Maria Laura; Gallucci, Giuseppina; Parrini, Iris; Turazza, Fabio Maria; Russo, Giulia; Maurea, Nicola; Quagliariello, Vincenzo; Lestuzzi, Chiara; Oliva, Stefano; Di Fusco, Stefania Angela; et al.
Abstract: The COVID-19 pandemic and its impact on patients with cancer and cardiovascular disease have confirmed the particular vulnerability of these populations. Indeed, not only a higher risk of contracting the infection has been reported but also an increased occurrence of a more severe course and unfavourable outcome. Beyond the direct consequences of COVID-19 infection, the pandemic has an enormous impact on global health systems. Screening programmes and non-urgent tests have been postponed; clinical trials have suffered a setback. Similarly, in the area of cardiology care, a significant decline in STEMI accesses and an increase in cases of late presenting heart attacks with increased mortality and complication rates have been reported. Health care systems must therefore get ready to tackle the 'rebound effect' that will likely show a relative increase in the short- and medium-term incidence of diseases such as heart failure, myocardial infarction, arrhythmias, and cardio- and cerebrovascular complications. Scientific societies are taking action to provide general guidance and recommendations aimed at mitigating the unfavourable outcomes of this pandemic emergency. Cardio-oncology, as an emerging discipline, is more flexible in modulating care pathways and represents a beacon of innovation in the development of multi-specialty patient management. In the era of the COVID-19 pandemic, cardio-oncology has rapidly modified its clinical care pathways and implemented flexible monitoring protocols that include targeted use of cardiac imaging, increased use of biomarkers, and telemedicine systems. The goal of these strategic adjustments is to minimize the risk of infection for providers and patients while maintaining standards of care for the treatment of oncologic and cardiovascular diseases. The aim of this document is to evaluate the impact of the pandemic on the management of cardio-oncologic patients with the-state-of-the-art knowledge about severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and coronavirus disease (COVID-19) in order to optimize medical strategies during and after the pandemic.